The diagnosis of food allergy: a systematic review and meta‐analysis. Issue 1 (14th December 2013) - Soares‐Weiser, K.; Takwoingi, Y.; Panesar, S. S.; Muraro, A.; Werfel, T.; Hoffmann‐Sommergruber, K.; Roberts, G.; Halken, S.; Poulsen, L.; van, R.; Vlieg‐Boerstra, B. J.; Sheikh, A.; et al.
Abstract Background We investigated the accuracy of tests used to diagnose food allergy. Methods Skin prick tests (SPT), specific‐IgE (sIgE), component‐resolved diagnosis and the atopy patch test (APT) were compared with the reference standard of double‐blind placebo‐controlled food challenge. Seven databases were searched and international experts were contacted. Two reviewers independently identified studies, extracted data, and used QUADAS‐2 to assess risk of bias. Where possible, meta‐analysis was undertaken. Results Twenty‐four (2831 participants) studies were included. For cows' milk allergy, the pooled sensitivities were 53% (95% CI 33–72), 88% (95 % CI 76–94), and 87% (95% CI 75–94), and specificities were 88% (95% CI 76–95), 68% (95% CI 56–77), and 48% (95% CI 36–59) for APT, SPT, and sIgE, respectively. For egg, pooled sensitivities were 92% (95% CI 80–97) and 93% (95% CI 82–98), and specificities were 58% (95% CI 49–67) and 49% (40–58%) for skin prick tests and specific–IgE. For wheat, pooled sensitivities were 73% (95% CI 56–85) and 83% (95% CI 69–92), and specificities were 73% (95% CI 48–89) and 43% (95% CI 20–69%) for SPT and sIgE. For soy, pooled sensitivities were 55% (95% CI 33–75) and 83% (95% CI 64–93), and specificities were 68% (95% CI 52–80) and 38% (95% CI 24–54) for SPT and sIgE. For peanut, pooled sensitivities were 95% (95% CI 88–98) and 96% (95% CI 92–98), and specificities were 61% (95% CI 47–74), and 59% (95% CI 45–72) for SPT and sIgE. Conclusions The evidence base is limited and weak and is therefore difficult to interpret. Overall, SPT and sIgE appear sensitive although not specific for diagnosing IgE‐mediated food allergy.